Teaching test taking skills - Rothman, Rosalind W; Cohen, Jill (Intervention In School And Clinic, 1988)
Many special education students have the knowledge but are unable or unprepared to demonstrate that knowledge while taking a test. © 1988, SAGE Publications. All rights reserved.
Keywords: dept.sed

Cognitive assessment with disabled readers - Spear, Louise C.; Sternberg, Robert J. (Special services in the schools, 1986)
This paper describes an approach to cognitive assessment that involves a synthesis of the traditional psychometric approach and the more recent information-processing approaches. In this combined approach, psychometric tests arc supplemented by tasks adapted from information-processing research. The paper focuses on the use of the approach with disabled readers, although the approach may be generalized to many different populations. The Test of Syllable and Phoneme Counting, a measure of awareness of the sound structure of speech, is described, as an example of an information-processing task that would be useful with younger disabled readers. Guidelines for using information-processing measures are also discussed. © 1986 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.sed

Research implications on choosing a program to teach about disabilities - Heinisch, BS (Rehabilitation Literature, 1981)
Keywords: Attitude to Health; Disabled Persons; Human; Individuality; Prejudice; Stereotyping; Teaching; attitude; dept.sed; disabled; education; musculoskeletal system; normal human; psychological aspect; school child; therapy; ⛔ No DOI found

Learning from Living: Dear Rachel - Kronick, Doreen; Rothman, Rosalind (Academic Therapy, 1980)
Keywords: dept.sed